WRITING WITH IMAGINATION : A CREATIVE APPROACH TO ENHANCING ELEMENTARY SCHOOL STUDENTS’ LITERACY - Sitorus, Friska Ria; Barus, Depitaria Br; Perangin-angin, Esra; Aurica, Jessy; Lestari, Nicholas (Bahasa Indonesia Prima, 2026)
Sanggar Anak Sungai Deli (Sasude) is a community-based learning center focused on educational and creative training activities. Its primary aim is to empower children living in the outskirts along the Deli River by nurturing their potential in various fields, including the arts, literature, environmental awareness, and other forms of creativity. This community service initiative aims to provide literacy mentoring to the children of the sanggar through an interactive and participatory writing approach. The core focus is to cultivate narrative thinking and self-expression through hands-on writing activities. The implementation process is structured into three systematic stages: planning, execution, and evaluation. During the implementation phase, participants were given the opportunity to write a narrative with the theme “I Will Become”, accompanied by visual illustrations to enhance the meaning of their writing. Following this, the children were encouraged to present their work in front of their peers as an exercise in oral literacy and confidence building. The results of the program indicate a notable improvement in the children’s understanding of literacy, particularly in selecting appropriate vocabulary, organizing ideas coherently, and articulating their thoughts verbally. More than just writing, the children began to grasp that literacy involves thinking critically, communicating effectively, and reflecting on the meaning behind their own narratives. These skills are expected to serve as a valuable foundation for their personal development in the future.